Solve for b 4=5/3*(-3)+b

Math
4=53⋅(-3)+b
Rewrite the equation as 53⋅(-3)+b=4.
53⋅(-3)+b=4
Simplify each term.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Factor 3 out of -3.
53⋅(3(-1))+b=4
Cancel the common factor.
53⋅(3⋅-1)+b=4
Rewrite the expression.
5⋅-1+b=4
5⋅-1+b=4
Multiply 5 by -1.
-5+b=4
-5+b=4
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Add 5 to both sides of the equation.
b=4+5
Add 4 and 5.
b=9
b=9
Solve for b 4=5/3*(-3)+b

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top